Correction to: My Home Quarantine on an App: A Qualitative Visual Analysis of Changes in Family Routines During the Covid-19 Pandemic in Chile (Qualitative Sociology, 2023 10.1007/S11133-023-09531-Z) - Vergara-Del Solar, A (Springer, 2023)
The institutional affiliations for José Antonio Román Brugnoli on the last page “Authors and Affiliations” must be expressed in Spanish in order to be recognized by that university. José Antonio Román Brugnoli’s correct affiliation is Departamento de Trabajo Social, Facultad de Humanidades y Tecnologías de la Comunicación Social, Programa Institucional de Fomento a la Investigación, Desarrollo e Innovación (PIDi), Universidad Tecnológica Metropolitana, Dieciocho 161, Santiago, Chile. © 2023, Springer Science+Business Media, LLC, part of Springer Nature.